Posted by **Bob Brown** on Tuesday, November 15, 2011 at 8:46am.

Cramer's rule

I understand the method but idk how to do this question

6x+2y=-44

-7+9Y=-96

## Answer this Question

## Related Questions

- Math - Solve using Determinants and Cramer's Rule? I was absent and missed the ...
- Algebra - I'm really lose with this problem...HELP Using Cramer Rule If D=O use ...
- Algebra II - 1) when using cramer's rule to solve the system of equations ...
- Algebra 1 - Use Cramer's rule to solve the system. -2x - 2y = -16 2x + 3y = 23
- Algebra - Use Cramer's rule to solve the following system of equations. If D=0, ...
- cramers rule - Solve the following linear system for x using Cramer’s rule. Show...
- Algebra - Use Cramer's Rule to solve each system of equations. a+b+5c=2 3a+b+2c=...
- algebra - I dont understand this question How would you explain to your friend ...
- Algebra 2(check pt 4) - 1)Cramer's Rule is used to solve the system of equations...
- solve using cramer's rule - solve using cramer's rule 3x+4y=-1 5x-2y=4